A Broadband X-Ray Investigation of Fast-spinning Intermediate Polar CTCV J2056–3014 - Ciro Salcedo; Kaya Mori; Gabriel Bridges; Charles J. Hailey; David A. H. Buckley; Raimundo Lopes de Oliveira; Gavin Ramsay; Anke van Dyk (The Astrophysical Journal)
We report on XMM-Newton, NuSTAR, and NICER X-ray observations of CTCV J2056–3014, a cataclysmic variable (CV) with one of the fastest-spinning white dwarfs (WDs) at P = 29.6 s. While previously classified as an intermediate polar, CJ2056 also exhibits the properties of WZ Sge–type CVs, such as dwarf novae and superoutbursts. With XMM-Newton and NICER, we detected the spin period up to ∼2 keV with 7 σ significance. We constrained its derivative to $|\dot{P}|\lt 1.8× {10}^{-12}$ s s ^−1 after correcting for binary orbital motion. The pulse profile is characterized by a single broad peak with ∼25% modulation. NuSTAR detected a fourfold increase in unabsorbed X-ray flux coincident with an optical flare, in 2022 November. The XMM-Newton and NICER X-ray spectra at 0.310 keV are best characterized by an absorbed, optically thin three-temperature thermal plasma model ( kT = 0.3, 1.0, and 4.9 keV), while the NuSTAR spectra at 3–30 keV are best fit by a single-temperature thermal plasma model ( kT = 8.4 keV), both with Fe abundance Z _Fe / Z _⊙ = 0.3. CJ2056 exhibits similarities to other fast-spinning CVs, such as low plasma temperatures and no significant X-ray absorption at low energies. As the WD’s magnetic field strength is unknown, we applied both nonmagnetic and magnetic CV spectral models ( MKCFLOW and MCVSPEC ) to determine the WD mass. The derived WD mass range ( M = 0.7–1.0 M _⊙ ) is above the centrifugal breakup mass limit of 0.56 M _⊙ and consistent with the mean WD mass of local CVs ( M ≈ 0.8–0.9 M _⊙ ).